Effect Of Hygrophila Spinosa Herbal Extract On Haemato Biochemical Profile Of Goats (Applied Biological Research, 2011)
The present investigation was aimed to study the haemato-biochemical profile in  grazing goats fed with the herbal extract of Hygrophila spinosa alone and in  combination with concentrate supplement. The herbal treatment improved the  haematological profile irrespective of concentrate supplementation in goats.  Herbal treatment and concentrate supplementation also improved serum iron  and copper concentration.
Keywords: Biochemical profile; cobalt; copper; goat; haemoglobin; Hygrophila spinosa; iron